Analysis of Risk Factors For Anemia and Neutropenia Post-Chemotherapy in Patients with Acute Lymphoblastic Leukemia at Samarinda Hospital - Aisyah, Siti; Azmi, Rizki Nur (Jurnal Ilmu Kesehatan, 2024)
Chemotherapy is the main therapy in the treatment of acute lymphoblastic leukemia and can change the body's hematological parameters during therapy. Haematological side effects that commonly occur after chemotherapy include anemia and neutropenia. The aim of this study was to determine the risk factors for anemia and neutropenia in patients with acute lymphoblastic leukemia after chemotherapy. This research is retrospective analytic with cross sectional data collection methods. The type of data used is secondary data from medical records of patients diagnosed with acute lymphoblastic leukemia. Data were analyzed using SPSS version 25.0. The research results obtained from this study were that there was a significant relationship between chemotherapy regimen and the incidence of anemia in acute lymphoblastic leukemia patients (p=0.001), and a significant relationship was found between age and chemotherapy regimen and the incidence of neutropenia in acute lymphoblastic leukemia patients (p= 0.005 and p=0.011). The conclusion obtained is that risk factors for chemotherapy regimens have a significant relationship between the incidence of anemia. In addition, the risk factors of age and chemotherapy regimen have a significant relationship between the incidence of neutropenia. Risk factors aged 12-25 years have the opportunity to increase the risk of neutropenia by 0.231 times greater than risk factors for chemotherapy regimens.